2008
DOI: 10.1123/rsj.32.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Satisfaction with Campus Recreation Facilities among College Students with Physical Disabilities

Abstract: The purpose of this study was to investigate satisfaction with campus recreation facilities among college students with physical disabilities. One hundred twenty-two college students with various physical disabilities participated in the study. This study found that use of and satisfaction with campus recreation facilities were significantly low among college students with disabilities. Specifically, 68% of college students with physical disabilities used campus recreation facilities less than 5 time per semes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 9 publications
0
18
1
Order By: Relevance
“…However, in this study, students with self-reported disabilities were just as likely to enter the recreation center than students without a selfreported disability. This finding is contradictory to those of Yoh, Mohr, and Gordon (2008). Yoh, et al's study examined the use of recreation facilities among college students with physical disabilities.…”
Section: Self-reported Disabilities: According To Healthy People 2010mentioning
confidence: 70%
See 1 more Smart Citation
“…However, in this study, students with self-reported disabilities were just as likely to enter the recreation center than students without a selfreported disability. This finding is contradictory to those of Yoh, Mohr, and Gordon (2008). Yoh, et al's study examined the use of recreation facilities among college students with physical disabilities.…”
Section: Self-reported Disabilities: According To Healthy People 2010mentioning
confidence: 70%
“…Only nine percent of female students with disabilities used the facilities more than five times in a semester, while fifty-eight percent of male students with disabilities used International Journal of Sport Management, Recreation & Tourism 22 school recreational facilities more than five times per semester. The authors are well aware that the institution where the Yoh, et al (2008) study was conducted was well equipped with programs and adaptable equipment that accommodated students with disabilities. Furthermore, research consistently reports that the physical activity and sport participation among people with disabilities is significantly lower than the general population (Gillespie, 2002;U.S.…”
Section: Self-reported Disabilities: According To Healthy People 2010mentioning
confidence: 99%
“…Yet, as Fujii and Woodard (2006) stated "accessibility refers to not only architecture but also to the programs provided and availability of information" (p. 6). Furthermore, Yoh, Mohr, and Gordon (2008) found in their study of the satisfaction level of college students with physical disabilities toward the recreation facilities on their campus that use and satisfaction with the recreational sport facilities by these students was significantly low, with over two-thirds of respondents claiming they used the facilities less than five times per semester. The implication of this finding is that while campus recreation administrators and staff may be in compliance with ADA regulations in terms of the accessibility of their facilities, accessibility of programs and information must also be high priorities.…”
Section: Discussionmentioning
confidence: 99%
“…Individual studies of undergraduate students with disabilities reported 90% of students with disabilities never attended an organized campus recreation event as a participant or spectator, and 88% reported never utilizing facilities during open recreation (Hodges, 2000). In addition, the level of participation in physical activity among persons with a disability declines during adolescence and sees the most rapid decline during the college years (Yoh et al, 2008). These findings suggest that recreational activities and intramural sports participation by students with disabilities differ significantly from that of traditional students (Hodges, 2000).…”
Section: Status Of Recreation Programming For Individuals With Disabilities On University Campusesmentioning
confidence: 99%